Pengaruh Kompetensi dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Kebudayaan Kota Palembang - Afif, M. Bariq Naufal; Kurniawan, Mohammad; Veronica, Meilin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study was to determine the effect of competence and work discipline on the performance of employees at the Palembang city cultural service. This study used quantitative and primary data by distributing questionnaires to employees of the cultural office of the city of Palembang. The population in this study were 60 respondents with a sampling technique using the slovin formula with ordinal scale measurements. The data were processed through the SPSS version 24 program with multiple linear regression analysis techniques. The results of this study indicate that competence has a positive and significant effect on employee performance, while work discipline has no effect on employee performance. From the results of the t test proves that competence has a partial effect on employee performance, work discipline has a partial effect on employee performance. Then the results of the f test prove competence and work discipline simultaneously affect employee performance by looking at the Fcount value that isgreater than Ftable, namely (44.985 > 3.16) with a significance value of 0.000 <0.05. The competency variable is the variable that has the greatest influence on employee performance at the Palembang city cultural service.